Magahi Language and Magadh - Mahato, Bir Bahadur (Bhashalok भाषालोक, 2026)
Magahi is an Indo-Aryan language, spoken in Eastern part of India and Nepal. Magahi is one of the national languages spoken in Nepal. It is mainly spoken in Sarlahi, Mahottari, Dhanusha, Sirha, Saptari, Sunsari, Morang, Jhapa and Kathmandu, the capital city of Nepal. It is genealogically related to Magadhi Apabhramsa, once having the status of rajbhasha, during the reign of Emperor Ashoka. The paper outlines the Magahi language in historical context along with its present status. The paper is also a small endeavour to capture the history of Magadh. The paper discusses that once a history of Magadh constituted the history of Bharatbarsha. The paper also attempts to discuss the people and culture of present Magadh.